The ChatGPT revolution : how conversational AI is transforming customer service and business operations - Behl, Abhishek; Krishman, Chitra; Malik, Priyanka; Gautam, Shalini (Emerald Publishing Limited, 2025)
Delving into ChatGPTs architecture and ability to generate human-like text, chapters go beyond technical explanations, exploring the factors contributing to ChatGPT's widespread adoption and its significance in society and industry. The work showcases how ChatGPT has transformed conversational experiences, revolutionizing customer service, streamlining business processes, and enhancing user engagement across various domains. Authors address the potential pitfalls and ethical concerns associated with ChatGPT. They delve into bias, misinformation, and the potential amplification of harmful content that may arise, as well as revealing insights into responsible AI practices, transparency, and accountability, emphasizing the importance of mitigating these risks and ensuring fairness in AI-driven conversations. Thoroughly examining the impact of ChatGPT on the workforce and the potential for job displacement, the need for upskilling and reskilling, and the importance of balanced integration of human oversight in chatbot interactions, the concept of collaborative human-AI systems is explored, where ChatGPT works alongside humans to enhance conversation quality and foster trust. The ChatGPT Revolution is essential reading for AI researchers and academics interested in the technical intricacies of ChatGPT, industry professionals in AI and NLP seeking practical insights for real-world applications, and ethics and responsible AI practitioners focusing on mitigating ethical concerns.
Keywords: Customer services -- Technological innovations.; Chatbots.; Artificial intelligence.; Business & Economics -- Customer Relations.; Customer services.; elektronické knihy; electronic books